0491 Sleep among Adolescents in Juvenile Detention. (25th May 2022) - Levenson, Jessica; London, Sarah; Ekas, Deana; Woods, Mary; Vojtash, Misty; Mulvey, Edward; Miller, Elizabeth
Abstract: Introduction: Adolescents involved in the juvenile justice system demonstrate high rates of psychiatric disorders, suicidality, and trauma, all of which is associated with poor sleep. Poor sleep is common among adolescents and is associated with numerous adverse outcomes like inattention, school absenteeism, emotion dysregulation, and substance use, outcomes that are related to juvenile justice system involvement. Yet very little is known about the sleep of adolescents involved in the juvenile justice system. We conducted a medical chart review and survey of detained adolescents to describe the sleep patterns and problems among these youth. Methods: We reviewed a random sample (26%) of the medical charts of youth detained in a juvenile detention center (n=31) over four days in Summer 2021. We reviewed all medical encounters in the month prior to the date of chart review. Additionally, 13 youth completed the Patient Reported Outcome Measurement Information System Pediatric Sleep Disturbance Short Form (PROMIS-SD). Twelve of them reported their sleep patterns while in detention. Results: Sleep was mentioned in 23% of all medical encounters, 62% of which indicated poor sleep. Sleep treatment was documented in 24% of notes, all consisting of pharmacotherapy. A sleep diagnosis was documented on 37% of billing sheets of all youth seen by a medical provider in the detention center in July 2021. On average, participants reported lights out around 9pm (SD=35min), sleep onset latency of 74mins (SD=75mins), wake time after sleep onset of 20 minutes (SD=16mins), and wake-up time of 7:50am (SD=67min). Youth reported average sleep duration of more than 9 hours while detained (SD=103mins). Average PROMIS-SD score was 66.2 (range 51.5-79.1) Conclusion: Though most youth obtain the recommended amount of sleep while detained, sleep disturbance is highly common among this population and average sleep disturbance is more than one standard deviation above the average. These data may inform the type of sleep interventions that are most relevant to detained youth. Future work should focus on further examining the sleep of adolescents in the juvenile justice system and identifying feasible, acceptable, and useful strategies for implementing evidence-based sleep interventions in this setting. Support (If Any): Dr. Levenson's effort was supported by K23HD087433